2014
DOI: 10.1016/j.jcrs.2013.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mitomycin-C on tear film, corneal biomechanics, and surface irregularity in mild to moderate myopic surface ablation: Preliminary results

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…However, Pentacam measured a significant increase (nearly 2‐fold, P < .05) in SA and RMS of corneal higher order aberrations after PRK (Tables and ). The A‐E and E‐B interfaces showed a much lower change in coneal aberrations, which supports the minimal change in ocular aberrations after low to moderate myopia PRK . In fact, the data from A‐E and E‐B interfaces showed that corneal higher order aberrations were minimally affected by the surgery (Tables and ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, Pentacam measured a significant increase (nearly 2‐fold, P < .05) in SA and RMS of corneal higher order aberrations after PRK (Tables and ). The A‐E and E‐B interfaces showed a much lower change in coneal aberrations, which supports the minimal change in ocular aberrations after low to moderate myopia PRK . In fact, the data from A‐E and E‐B interfaces showed that corneal higher order aberrations were minimally affected by the surgery (Tables and ).…”
Section: Discussionsupporting
confidence: 62%
“…Spherical aberration was the most affected after PRK ( P < .05) . Using Scheimplfug corneal imaging, there was hardly any corneal aberrometric changes noted after PRK . Using Scheimpflug imaging, another study reported a significant increase in anterior corneal higher order aberrations (mean spherical equivalent was less than −4D) .…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that MMC application during the PRK procedure does not cause additional changes in biomechanical properties. 13,14 In a study by Wang et al 15 comparing SMILE and LASIK, CH values were significantly lower after SMILE. They found that the difference in CH was especially large when correcting myopia of -6.00 D or more.…”
Section: Discussionmentioning
confidence: 97%
“…7,10,13,14,15,16,17 Several studies have evaluated the changes in biomechanical properties resulting from laser-assisted in situ keratomileusis (LASIK) and PRK, which have been employed for many years to treat myopia, as well as the SMILE procedure, a more current treatment method. 7,10,13,14,15,16 Although there are studies comparing LASIK with PRK and with SMILE in terms of their effects on corneal biomechanical properties, 7,16,17 our study is the first to compare corneal biomechanical aspects of the SMILE and PRK procedures in the treatment of myopia. In the current study, CH and CRF were used to evaluate corneal biomechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages after an operation, ocular surface functions may be affected because of the cytotoxicity of this drug. Nevertheless, at a 6 month follow-up, the use of mitomycin C did not appear to contribute significantly to surface irregularities or tear-film dysfunction [ 30 , 32 , 33 ]. Therefore, in order to eliminate the influence of mitomycin C, the patients who had undergone trabeculectomy at lease 6 months were recruited.…”
Section: Discussionmentioning
confidence: 99%